A Step-by-step Protocol for Obtaining Mature Microglia from Mice - Min- You; Min- Kwon (Bio-Protocol, 2022)
In mice, microglial precursors in the yolk sac migrate to the brain parenchyma through the head neuroepithelial layer between embryonic days 8.5 (E8.5)–E16.5 and acquire their unique identity with a ramified form. Based on the microglial developmental process, we dissected the neuroepithelial layer (NEL) of E13.5 mice, which is composed of microglial progenitor and neuroepithelial cells. The NEL was bankable and expandable. In addition, microglial precursors were matured according to NEL culture duration. The matured microglia (MG; CD11b-positive cells) were easily isolated from the cultured NEL using a magnetic-activated cell sorting system and named NEL-MG. In conclusion, we obtained higher yields of adult-like microglia (mature microglia: NEL-MG) compared to previous in vitro surrogates such as neonatal microglia and microglial cell lines. Graphical abstract: